The impact of battery storage technologies in residential buildings with sub-daily autonomy and EV contribution. (November 2019) - Chatzivasileiadi, Aikaterini; Ampatzi, Eleni; Knight, Ian P.
Abstract: This study has been undertaken to gain a better understanding regarding the choice and impact of battery storage technologies in a use case with contribution of an electric vehicle to the overall domestic consumption. The study assessed the storage requirements of nine battery technologies for different residential building scales at the distribution level considering sub-daily autonomy periods. The use case explored in this paper assumed that the battery from an electric vehicle could contribute to the overall domestic consumption during the required hours of storage based on a scenario addressing demand response through peak shifting in 2030 (DR 2030) from an earlier study. After deriving the nominal capacity for each battery technology, the spatial requirements, including footprint, volume and mass, as well as the cost, for the scales of interest were estimated. The study showed that space and cost savings of up to 90% compared to a use case that do not consider EV contribution could be achieved. The choice of the most suitable technology according to its applicability in different building scales and different use cases should be carefully assessed.